INTEGRATION OF CIRCULAR ECONOMY PRINCIPLES INTO STATE POLICY IN FOREST SECTOR - Shkodina, Iryna; Nykytiuk , Valentyna (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The report examines the theoretical and practical foundations of integrating circular economy  principles into state forestry policy. It reveals the essence of the closed-loop concept and the cascading  use of wood. The mechanism for converting waste into valuable resources and energy is  demonstrated. Particular attention is paid to the challenges Ukraine faces on the path to circularity: from raw  material dependence and bureaucratic barriers to the necessity of technological re-equipment.  Strategic recommendations for state policy are formulated, including "green" public procurement,  financial incentives, digitalization of the industry via the "Diia.Business" platform, and the creation  of forest clusters based on the examples of Finland and Austria. It is substantiated that the transition  to a circular model is a key factor in European integration and the development of a high-tech  bioeconomy in Ukraine